Adenocarcinoma arising from a gastric duplication cyst with invasion to the stomach: a case report with literature review. Issue 4 (26th March 2004) - Kuraoka, K; Nakayama, H; Kagawa, T; Ichikawa, T; Yasui, W
Abstract : This report describes a rare case of adenocarcinoma arising from a gastric duplication cyst, with invasion to the stomach wall, in a 40 year old Japanese man. A cystic lesion was found between the stomach and the spleen. The cyst had a well circumscribed smooth muscle layer, corresponding to the muscularis propria of the stomach and the mucosa of the alimentary tract. A well differentiated adenocarcinoma was found within the duplication cyst, invading its serosa. Well differentiated adenocarcinoma was independently found in the fundus of the stomach; the tumour of the cyst was connected by fibrous tissue. Microscopically, there was neither adenocarcinoma in situ nor precancerous lesions, such as epithelial dysplasia, suggesting that the carcinoma derived from a gastric duplication cyst that invaded the stomach. Duplication cysts should be included in the differential diagnosis of cystic masses of the gastrointestinal tract, and the possibility of malignancy within these cysts should be considered.